Extrapulmonary tuberculosis in Morocco: A systematic review of observational studies - Mohamed Dellal; Sanaa Batoui; Ahmed Chetoui; Mohamed Kanouf; Touria Fatihi; Khalid Habbari (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Background: Tuberculosis remains a major global health concern and a leading cause of mortality. In Morocco, various forms of extrapulmonary tuberculosis are prevalent. This systematic review examines research findings on the prevalence, risk factors, and treatment outcomes of extrapulmonary tuberculosis in Morocco. Methods: We conducted searches for observational studies on extrapulmonary tuberculosis in Morocco, published between January 1991 and February 2023, using Scopus, ScienceDirect, and PubMed databases. Medical Subject Heading keywords were used to guide the search. Results: This review included 18 studies focusing on different forms of extrapulmonary tuberculosis, such as cold abscesses, lymph nodes, meningeal, cutaneous, osteoarticular, genital, breast, and gastrointestinal tuberculosis. These studies provided insights into the clinical, diagnostic, and therapeutic aspects of these extrapulmonary tuberculosis forms. Prevalence data were limited, and treatment outcomes varied considerably across studies. The only study providing prevalence data for all forms of extrapulmonary tuberculosis reported a prevalence of 43.5% among tuberculosis cases in Larach Province. Treatment success rates ranged from 64.7% to 100%. Common risk factors included low socioeconomic status, diabetes mellitus, pulmonary tuberculosis exposure, and HIV co-infection. Conclusions: This review highlights a lack of comprehensive on the prevalence of extrapulmonary tuberculosis in Morocco, with inconsistent findings on risk factors and treatment outcomes. Further controlled studies are recommended to obtain more robust evidence and inform more effective management strategies for extrapulmonary tuberculosis.